Significações constituídas pelas equipes gestoras sobre as relações de igualdade racial na escola - Freitas, Elenir Fagundes Santos (2018)
The school management team’s role is fundamental for the construction of the pedagogical-political project. Mobilizing educators so that they reflect upon how racial relations are configured in the school environment, stimulating the construction of new learning in the ethnic-racial field, contributes to overcoming racism in school and quality education. The present research has as objective to apprehend the meanings attributed by management teams regarding racial equality relations in the school environment, having as locus two municipal schools in São Bernardo do Campo. Semi-structured interviews were carried out with two management teams (school principals and school pedagogical coordinators) for this study. The study was outlined from the literature review of researchers like Munanga (2005), Gomes (2012), Ribeiro (2018) and Ronca (2016), settled in the methodological and theoretical reasoning of sociohistorical psychology (BOCK, 2009) and supported by dialectical-historical materialism method. During the interview, the management teams’ meanings concerning racism phenomenon in Brazilian society and how racial relations are established in the school environment, the activity carried out by educators in the ethnic-racial field, as well as possibilities for overcoming the phenomenon in school are discussed. The analysis was conducted through the development of the pre-indicators, indicators and Nuclei of Meaning from Aguiar and Ozella (2006). From the narratives, it was identified that racism in the school environment presents itself in a veiled, naturalized way or reduced to bullying. There is an absence of reflection on the subject at school, and an omission regarding the care provided to black children who experience racial inequality. Racial conflicts are resolved without reflecting on their causes and there is also an absence of regards toward the ethnic-racial field in textbooks, legitimizing racism in the school space. Other findings reveal the importance of unveiling the phenomenon in the school space through the training of educators. The development of work with the theme on a day-to-day basis and attention to the care provided to children who undergo racial slurs were pointed out. It was also revealed that the LDB implementation through the law 10639/3, contemplating African-Brazilian and African history and culture contents in the pedagogical-political project, expands the cultural capital of children and enables the overcoming of racism at school